Efficient evaluation of bridge deformation for running safety of railway vehicles using simplified models. Issue 3 (February 2020) - Jin, Zhibin; Yuan, Ligang; Pei, Shiling
The running safety of high-speed trains over bridges is a great concern in bridge design. Typically, the running safety of vehicles is evaluated by vehicle–track simulations that are computationally expensive and unfamiliar to bridge designers. This study investigates simplified vehicle–track models for assessing the running safety of vehicles on deformed bridges. Four types of simplified vehicle models along with four types of simplified wheel–track models are investigated. The predicted wheel–rail forces are compared with those simulated by the detailed vehicle–track program. In these simulations, typical bridge deformations are taken as excitations to the dynamic system. It is found that omitting the rail vibration leads to large wheel–rail response errors. The wheel–rail constraint model gives similar wheel–rail responses to those obtained by the Hertz contact model. A vehicle–track model with five degrees-of-freedom is adequate for assessing wheel–rail forces. Furthermore, an analytical solution to the wheel–rail forces running over an angular rotation was obtained. These simplified vehicle–track models provide an efficient way to assess the running safety of vehicles on deformed bridges when using probabilistic or optimal analyses that require a large number of simulations.